The turner house ebook - Flournoy, Angela (2015)
NATIONAL BOOK AWARD FINALIST A New York Times Notable Book • An Amazon Top 100 Editors' Pick of the Year Named a Best Book of the Year by O, The Oprah Magazine • Entertainment Weekly • NPR • Essence • Men's Journal • Buzzfeed • Bustle • Time Out • Denver Post • Publishers Weekly • Kirkus Reviews • BookPage • Literary Hub • Kobo • The Week • Detroit Free Press Winner of the Paterson Fiction Prize and the Black Caucus of the ALA—1st Novelist Award Nominated for the International Dublin Literary Award, the NAACP Image Award for Outstanding Literary Work – Debut Author, and the Hurston/Wright Legacy Award for Fiction Finalist for the New York Public Library Young Lions Award, the VCU Cabell First Novelist Award, and the Indies Choice Award Short-listed for the PEN/Robert W. Bingham Prize for Debut Fiction, the Center for Fiction First Novel Prize, the Ernest Gaines Award, The Morning News Tournament of Books, the Winter Lariat List, and the Medici Book Club Prize Long-listed for the NBCC John Leonard Prize for A Debut Novel and the Chautauqua Prize A powerful debut, The Turner House marks a major new contribution to the story of the American family. The Turners have lived on Yarrow Street for over fifty years. Their house has seen thirteen children grown and gone—and some returned; it has seen the arrival of grandchildren, the fall of Detroit's East Side, and the loss of a father. The house still stands despite abandoned lots, an embattled city, and the inevitable shift outward to the suburbs. But now, as ailing matriarch Viola finds herself forced to leave her home and move in with her eldest son, the family discovers that the house is worth just a tenth of its mortgage. The Turner children are called home to decide its fate and to reckon with how each of their pasts haunts—and shapes—their family's future. Praised by Ayana Mathis as "utterly moving" and "un-putdownable," The Turner House brings us a colorful, complicated brood full of love and pride, sacrifice and unlikely inheritances. It's a striking examination of the price we pay for our dreams and futures, and the ways in which our families bring us home.